A new mixed micellar preparation for oral vitamin K prophylaxis: randomised controlled comparison with an intramuscular formulation in breast fed infants. Issue 4 (1st October 1998) - Greer, Frank R; Marshall, Sharon P; Severson, Rebecca R; Smith, David A; Shearer, Martin J; Pace, Daniel G; Joubert, Pieter H
Abstract : OBJECTIVE: To compare a new oral preparation of vitamin K1 (Konakion MM) containing lecithin and glycocholic acid with a standard intramuscular (IM) preparation during the first 8 weeks of life in exclusively breast fed infants. METHODS: Infants were randomised at birth to the IM group (1 mg vitamin K) or the oral group (2 mg given at birth and repeated at 7 and 30 days of life). Prothrombin time (INR), plasma vitamin K1, and PIVKA II (undercarboxylated prothrombin) were monitored at 14, 30, and 56 days of age. RESULTS: Seventy nine infants were randomised to the oral group and 77 to the IM group. Sixty seven infants in each group completed eight weeks of the study. Prothrombin times did not differ between the two groups. Mean (SD) plasma vitamin K1 values (in ng/ml) decreased in both groups over time, but were higher in the oral group at 14 and 56 days: 2.0 (1.6) v 1.3 (1.1) at 14 days; 0.5 (0.3) v 0.5 (0.7) at 30 days; and 0.5 (0.8) v 0.2 (0.2) at 56 days of life. PIVKA II was raised (⩾ 0.1 AU/ml) in cord blood in 47% of the infants. By 14 days, only one infant in each group had a raised PIVKA II value and both of these initially had high concentrations of PIVKA II in cord blood. At 30 days, there were no raised PIVKA II values. At 56 days, there were no raised PIVKA II values in the oral group, although three infants in the IM group had raised values. CONCLUSIONS: Plasma vitamin K concentrations were at least equal or significantly higher in babies given oral vitamin K supplements compared with IM treated babies at the time points measured. Through the first 8 weeks of life, multiple doses of the new oral preparation maintain haemostasis and vitamin K status in breast fed infants at least equal to that of the intramuscular preparation.